Coal gangue-based surface molecular imprinting adsorption material and preparation method thereof
By modifying the coal gangue powder and performing surface molecular imprinting reaction, a coal gangue base surface molecular imprinting adsorption material with a high specific surface area and suitable pore structure was prepared, which solved the shortcomings of the existing carrier in terms of physical strength and stability, and achieved the Efficient adsorption and selective separation, environmentally friendly process and high resource utilization efficiency.
Patent Information
- Application Number
- CN202411771735.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-02-07
AI Technical Summary
The existing carriers have shortcomings in terms of physical strength and stability, and are cost-effective and difficult to modify, which affects environmental protection performance.
Using coal gangue as a support, the modified coal gangue powder is treated by calcining and acid leaching, and surface molecular imprinting reaction is carried out under an inert atmosphere to prepare a coal gangue base surface molecular imprinting adsorption material with a high specific surface area and a suitable pore structure.
It significantly improves the adsorption capacity and selectivity of the material, meets the needs of efficient separation and detection, and has high chemical stability, extends service life, and has environmentally friendly processes and high resource utilization efficiency.
Smart Images

Figure CN119386837A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of imprinted polymer preparation, and relates to a gangue-based surface molecular imprinted adsorption material and a preparation method thereof. Background Art
[0002] Molecular imprinting technology is an advanced method for preparing materials with specific selective recognition capabilities. Its basic principle is to introduce target molecules into polymers to form "imprinted" holes with target molecule characteristics during the polymerization process. After removing the target molecules, these imprinted holes can specifically bind or recognize the same or similar molecules, thereby achieving efficient molecular recognition and separation.
[0003] In molecular imprinting technology, the selection and design of carriers are crucial, because the carrier not only provides a matrix for forming imprinted pores, but also directly affects the performance of the imprinted material. A high-quality carrier should have good chemical stability, appropriate pore structure and high specific surface area to ensure that the target molecule can effectively form imprinted pores and maintain its specificity and stability after the target molecule is removed. Commonly used carriers include imprinted adsorption materials with carbon nanoparticles as carriers, imprinted adsorption materials with graphene aerogels as carriers, and imprinted adsorption materials with porous ceramics as carriers disclosed in the prior art.
[0004] Compared with other common carriers, many traditional carriers such as activated carbon, silica gel and resin are usually more expensive and difficult to modify, and lack physical strength and stability. The production process of these carriers may also have a certain impact on the environment. Summary of the invention
[0005] The purpose of the present invention is to solve the problems in the prior art that the existing carriers have high cost and modification difficulty, and are insufficient in physical strength and stability, and to provide a gangue-based surface molecular imprinting adsorption material and a preparation method.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The present invention provides a method for preparing a gangue-based surface molecularly imprinted adsorption material, comprising the following steps:
[0008] calcining and acid leaching the gangue powder to obtain modified gangue powder;
[0009] Using modified gangue powder as a carrier, phenol and methacrylic acid were added to acetonitrile solvent under an inert atmosphere for a preliminary reaction, and then a cross-linking agent and an initiator were added to carry out a surface molecular imprinting reaction to obtain an imprinting reaction product.
[0010] The imprinting reaction product is treated to obtain the gangue-based surface molecular imprinting adsorption material.
[0011] Preferably, the modified coal gangue powder is obtained by:
[0012] The coal gangue is ground to 200-300 meshes; the coal gangue powder is calcined at 700-800°C; and then acid-leached with 12-14 mol / L hydrochloric acid to obtain modified coal gangue powder.
[0013] Preferably, the calcination time is 3 h to 5 h, and the acid leaching time is 4 h to 6 h.
[0014] Preferably, the mass ratio of phenol, modified coal gangue powder and methacrylic acid is (1.0-1.2):(0.8-1.0):(3-5).
[0015] Preferably, the added crosslinking agent is ethylene glycol dimethacrylate, and the added initiator is azobisisobutyronitrile.
[0016] Preferably, the mass ratio of ethylene glycol dimethacrylate to azobisisobutyronitrile is (1-2):(0.15-0.20).
[0017] Preferably, the temperature of the preliminary reaction is controlled at 20°C to 30°C, and the reaction time of the preliminary reaction is 1h to 2h;
[0018] The temperature of the surface molecular imprinting reaction is controlled at 60°C to 70°C, and the reaction time of the surface molecular imprinting reaction is 22h to 24h;
[0019] The above reactions were all carried out under an inert atmosphere, which was formed by introducing nitrogen into the reaction system and sealing it.
[0020] Preferably, the imprinting reaction product is treated to obtain a gangue-based surface molecular imprinting adsorption material, specifically:
[0021] The imprinting reaction product is placed in an eluent and stirred, and vacuum dried to obtain a gangue-based surface molecular imprinting adsorption material;
[0022] The eluent is a mixture of methanol and acetic acid.
[0023] Preferably, the volume ratio of methanol to acetic acid is 9:1 to 9:2; the stirring time is 22 hours to 24 hours; and the vacuum drying is carried out in a vacuum freeze dryer for 12 hours to 14 hours.
[0024] A gangue-based surface molecular imprinting adsorption material is prepared by adopting a method for preparing a gangue-based surface molecular imprinting adsorption material.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The present invention provides a method for preparing a gangue-based surface molecular imprinting adsorption material. Since gangue has a large specific surface area and an excellent pore structure, gangue can be effectively used to prepare a selective adsorption material through appropriate treatment and modification. Therefore, the present application uses gangue as a carrier and phenol as a template molecule to synthesize an adsorbent with high selectivity and specific recognition ability for phenol molecules through molecular imprinting technology. Through a simple calcination and modification process, gangue is successfully converted into a surface molecular imprinting adsorption material with a large specific surface area and a suitable pore structure. This process significantly improves the adsorption capacity and selectivity of the material, meeting the needs of efficient separation and detection. The material shows excellent selectivity in a mixed solution of various phenol molecules such as phenol, hydroquinone and p-nitrophenol, demonstrating its wide application potential in the fields of adsorption, separation and detection. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0028] Figure 1 It is a scanning electron microscope analysis diagram of the coal gangue of Example 1 (a), a scanning electron microscope analysis diagram of the modified coal gangue powder (b), and a scanning electron microscope analysis diagram of the coal gangue-based surface molecular imprinting adsorption material (c).
[0029] Figure 2 It is the X-ray diffraction spectrum of the coal gangue and modified coal gangue powder in Example 1.
[0030] Figure 3 It is the thermogravimetric analysis diagram of the gangue-based surface molecular imprinting adsorption material of Example 1 (a), the specific surface area analysis diagram of gangue and the gangue imprinted material (b) and the pore structure analysis diagram of gangue and the gangue imprinted material (c).
[0031] Figure 4 This is the selective adsorption performance of the gangue-based surface molecular imprinting adsorption material in Example 1. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. The components of the embodiments of the present invention described and provided in the drawings herein can be arranged and designed in various different configurations.
[0033] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] It should be noted that similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, further definition and explanation thereof is not required in subsequent drawings.
[0035] The present invention is further described in detail below in conjunction with the accompanying drawings:
[0036] The present invention provides a method for preparing a gangue-based surface molecular imprinting adsorption material, comprising the following steps:
[0037] Step 1, raw material pretreatment: First, grind the large pieces of coal gangue to 200-300 mesh; then, calcine the powder at 700-800°C for 3-5 hours; then, use 12mol / L-14mol / L hydrochloric acid for acid leaching for 4-6 hours; finally, obtain modified coal gangue powder.
[0038] Step 2, gangue imprinting treatment: modified gangue powder is used as a carrier, and in an inert atmosphere, phenol template molecules and methacrylic acid functional monomers are first added to acetonitrile solvent (25mL-30mL) for preliminary reaction; nitrogen is introduced for 5min-10min during the preliminary reaction, and then sealed, and magnetic stirring is performed at 20-30°C for 1h-2h, and the stirring speed is 400r / min-450r / min. Subsequently, ethylene glycol dimethacrylate is added as a crosslinking agent and azobisisobutyronitrile is added as an initiator to perform surface molecular imprinting reaction; when performing surface molecular imprinting reaction, nitrogen is introduced again for 5min-10min, and then sealed, and magnetic stirring is performed at 60-70°C for 22-24h, and the stirring speed is 400r / min-450r / min. This process effectively fixes the template molecules and functional monomers on the pore structure of the gangue carrier, and finally obtains the imprinting reaction product.
[0039] The mass ratio of phenol, modified gangue powder and methacrylic acid is (1.0-1.2): (0.8-1.0): (3-5); the mass ratio of ethylene glycol dimethacrylate and azobisisobutyronitrile is (1-2): (0.15-0.20).
[0040] Step 3, demoulding treatment of imprinting: the imprinting reaction product is placed in a mixture of methanol and acetic acid (ratio of 9:1 to 9:2) and stirred for 22 to 24 hours, and then vacuum dried to obtain the final coal gangue-based surface molecular imprinting adsorption material.
[0041] Wherein, the vacuum drying is carried out in a vacuum freeze dryer for a drying time of 12 to 14 hours.
[0042] Example 1
[0043] Raw material pretreatment: First, the large pieces of coal gangue were ground to 200 mesh (see the attached SEM analysis). Figure 1 a); then, the powder was calcined at 700°C for 3 h, and then acid-leached with 12 mol / L hydrochloric acid for 4 h to obtain modified gangue powder (the scanning electron microscope analysis of which is shown in the attached Figure 1 c).
[0044] Take 1g of phenol, 0.8g of modified coal gangue powder and 3mL of methacrylic acid, dissolve them in 25mL of acetonitrile solvent, introduce nitrogen for 5 minutes and then seal, and magnetically stir for 1h at 30℃ with a stirring speed of 400r / min; then add 1mL of ethylene glycol dimethacrylate and 0.15g of azobisisobutyronitrile, introduce nitrogen again for 5 minutes and then seal, and magnetically stir for 22h at 60℃ with a stirring speed of 400r / min. Phenol and methacrylic acid modify the pores of the modified coal gangue to obtain an imprinted product.
[0045] The imprinted product obtained above was eluted with a methanol / acetic acid mixture (ratio 9:1) and stirred for 22 hours to remove the phenol template molecules on the imprinted reaction product. The washed imprinted reaction product was dried in a vacuum freeze dryer for 12 hours to finally obtain a gangue-based surface molecular imprinted adsorption material (the scanning electron microscopy analysis of which is shown in the attached Figure 1 c).
[0046] 0.2 g of gangue-based surface molecular imprinting adsorption material was taken and adsorbed with 20 mL of phenol solution with a mass concentration of 500 mg / L. The adsorbed solution samples were extracted at set times (5, 10, 15, 20, 30, 40, 60, 80, 100 and 120 min), and the phenol content was determined by ultraviolet spectroscopy to calculate the adsorption amount of gangue-based surface molecular imprinting adsorption material (the adsorption kinetic curve is shown in the attached figure). Figure 4 ).
[0047] Take 0.2g of gangue-based surface molecular imprinting adsorption material and 0.2g of gangue, and place them in 20mL of phenol, hydroquinone and p-nitrophenol mixed solution, where the mass concentration of the three in the mixed solution is 500 mg / L. Extract the adsorbed solution sample within the set time of 60min, and determine the content of phenol, hydroquinone and p-nitrophenol by ultraviolet spectroscopy to calculate the selectivity of the adsorption material (the adsorption selectivity is shown in the attached Figure 4 ).
[0048] Scanning electron microscopy (see Appendix Figure 1 ) and found that the surface pores of the modified gangue powder were significantly enlarged and the roughness increased. In contrast, the surface of the gangue was relatively smooth. The gangue-based surface molecular imprinting adsorption material formed an obvious coating imprinting layer on the surface and a large number of micropores appeared.
[0049] The X-ray diffraction pattern (see Appendix Figure 2 ) It can be clearly seen that after high-temperature calcination and acidification treatment, the coal gangue is transformed into kaolinite, and its specific surface area and stability are significantly improved, while its harmfulness is greatly reduced, making it safer and more environmentally friendly.
[0050] Thermogravimetric analysis (see attached Figure 3 In a), it can be clearly observed that the temperature decreases at around 554°C, which is caused by the thermal decomposition of functional monomers and crosslinking agents, indicating that the modification of functional monomers and other substances has been successfully completed. In addition, the specific surface area and pore structure analysis of coal gangue and coal gangue imprinted materials (see Appendix Figure 3 From the comparison between b and c), it can be seen that the number of micropores suitable for the size of phenol molecules in the modified coal gangue imprinted material is significantly increased.
[0051] Adsorption kinetics curve (see attached Figure 4 ) showed that the selective adsorption performance of gangue-based surface molecular imprinting adsorption materials for phenol, p-phenol diphenol, and p-nitrophenol was analyzed (see Appendix Figure 3 ), the results showed that the selectivity of this material for phenol, phenol diphenol and p-nitrophenol was significantly better than that of ordinary coal gangue.
[0052] Example 2
[0053] Raw material pretreatment: First, the large pieces of coal gangue were ground to 250 mesh; then, the powder was calcined at 750°C for 4 h; then, 13 mol / L hydrochloric acid was used for acid leaching for 5 h to finally obtain modified coal gangue powder.
[0054] Take 1g of phenol, 0.8g of modified coal gangue powder and 3mL of methacrylic acid, dissolve them in 30mL of acetonitrile solvent, introduce nitrogen for 10min and then seal, and magnetically stir for 1.5h at 20℃ with a stirring speed of 450r / min; then add 1mL of ethylene glycol dimethacrylate and 0.15g of azobisisobutyronitrile, introduce nitrogen again for 10min and then seal, and magnetically stir for 24h at 70℃ with a stirring speed of 450r / min. Phenol and methacrylic acid modify the pores of the modified coal gangue to obtain an imprinted product.
[0055] The imprinted product obtained above was eluted with a methanol / acetic acid mixture (ratio 9:1.5) eluent, stirred and eluted for 23 hours to remove the phenol template molecules on the imprinted reaction product. The washed imprinted reaction product was dried in a vacuum freeze dryer for 12 hours to finally obtain a gangue-based surface molecular imprinted adsorption material.
[0056] 0.2 g of gangue-based surface molecular imprinting adsorption material was taken and adsorbed with 20 mL of phenol solution with a mass concentration of 500 mg / L. Samples of the adsorbed solution were extracted at set times (5, 10, 15, 20, 30, 40, 60, 80, 100 and 120 min), and the content of phenol was determined by ultraviolet spectroscopy to calculate the adsorption amount of the gangue-based surface molecular imprinting adsorption material.
[0057] Take 0.2g of gangue-based surface molecular imprinting adsorption material and 0.2g of gangue, and place them in 20mL of phenol, hydroquinone and p-nitrophenol mixed solution, where the mass concentration of the three in the mixed solution is 500mg / L. Extract the adsorbed solution sample within the set time of 60min, and determine the content of phenol, hydroquinone and p-nitrophenol by ultraviolet spectroscopy to calculate the selectivity of the adsorption material.
[0058] Example 3
[0059] Raw material pretreatment: First, the large pieces of coal gangue were ground to 300 mesh; then, the powder was calcined at 800°C for 5 h; then, 14 mol / L hydrochloric acid was used for acid leaching for 6 h to finally obtain modified coal gangue powder.
[0060] Take 1g of phenol, 0.8g of modified coal gangue powder and 3mL of methacrylic acid, dissolve them in 28mL of acetonitrile solvent, introduce nitrogen for 8min and then seal, and magnetically stir for 2h at 25℃ with a stirring speed of 430r / min; then add 1mL of ethylene glycol dimethacrylate and 0.15g of azobisisobutyronitrile, introduce nitrogen again for 8min and then seal, and magnetically stir for 23h at 65℃ with a stirring speed of 430r / min. Phenol and methacrylic acid modify the pores of the modified coal gangue to obtain an imprinted product.
[0061] The imprinted product obtained above was eluted with a methanol / acetic acid mixture (ratio 9:2) and stirred for 24 hours to remove the phenol template molecules on the imprinted reaction product. The washed imprinted reaction product was dried in a vacuum freeze dryer for 14 hours to finally obtain a gangue-based surface molecular imprinted adsorption material.
[0062] 0.2 g of gangue-based surface molecular imprinting adsorption material was taken and adsorbed with 20 mL of phenol solution with a mass concentration of 500 mg / L. Samples of the adsorbed solution were extracted at set times (5, 10, 15, 20, 30, 40, 60, 80, 100 and 120 min), and the content of phenol was determined by ultraviolet spectroscopy to calculate the adsorption amount of the gangue-based surface molecular imprinting adsorption material.
[0063] Take 0.2g of gangue-based surface molecular imprinting adsorption material and 0.2g of gangue, and place them in 20mL of phenol, hydroquinone and p-nitrophenol mixed solution, where the mass concentration of the three in the mixed solution is 500mg / L. Extract the adsorbed solution sample within the set time of 60min, and determine the content of phenol, hydroquinone and p-nitrophenol by ultraviolet spectroscopy to calculate the selectivity of the adsorption material.
[0064] Example 4
[0065] Raw material pretreatment: First, the large pieces of coal gangue were ground to 200 mesh; then, the powder was calcined at 700°C for 3 h; then, 12 mol / L hydrochloric acid was used for acid leaching for 4 h to finally obtain modified coal gangue powder.
[0066] Take 1.1g of phenol, 0.9g of modified coal gangue powder and 4mL of methacrylic acid, dissolve them in 25mL of acetonitrile solvent, introduce nitrogen for 10min and then seal, and magnetically stir for 1.5h at 28℃ with a stirring speed of 425r / min; then add 1mL of ethylene glycol dimethacrylate and 0.15g of azobisisobutyronitrile, introduce nitrogen again for 10min and then seal, and magnetically stir for 24h at 70℃ with a stirring speed of 400r / min. Phenol and methacrylic acid modify the pores of the modified coal gangue to obtain an imprinted product.
[0067] The imprinted product obtained above was eluted with a methanol / acetic acid mixture (ratio 9:1.5) eluent, stirred and eluted for 23 hours to remove the phenol template molecules on the imprinted reaction product. The washed imprinted reaction product was dried in a vacuum freeze dryer for 12.5 hours to finally obtain a gangue-based surface molecular imprinted adsorption material.
[0068] 0.2 g of gangue-based surface molecular imprinting adsorption material was taken and adsorbed with 20 mL of phenol solution with a mass concentration of 500 mg / L. Samples of the adsorbed solution were extracted at set times (5, 10, 15, 20, 30, 40, 60, 80, 100 and 120 min), and the content of phenol was determined by ultraviolet spectroscopy to calculate the adsorption amount of the gangue-based surface molecular imprinting adsorption material.
[0069] Take 0.2g of gangue-based surface molecular imprinting adsorption material and 0.2g of gangue, and place them in 20mL of phenol, hydroquinone and p-nitrophenol mixed solution, where the mass concentration of the three in the mixed solution is 500mg / L. Extract the adsorbed solution sample within the set time of 60min, and determine the content of phenol, hydroquinone and p-nitrophenol by ultraviolet spectroscopy to calculate the selectivity of the adsorption material.
[0070] Example 5
[0071] Raw material pretreatment: First, the large pieces of coal gangue were ground to 200 mesh; then, the powder was calcined at 700°C for 3 h; then, 12 mol / L hydrochloric acid was used for acid leaching for 4 h to finally obtain modified coal gangue powder.
[0072] Take 1.2g of phenol, 1.0g of modified coal gangue powder and 5mL of methacrylic acid, dissolve them in 30mL of acetonitrile solvent, introduce nitrogen for 8min and then seal, and magnetically stir for 1.5h at 25℃ with a stirring speed of 400r / min; then add 1mL of ethylene glycol dimethacrylate and 0.15g of azobisisobutyronitrile, introduce nitrogen again for 10min and then seal, and magnetically stir for 23h at 70℃ with a stirring speed of 450r / min. Phenol and methacrylic acid modify the pores of the modified coal gangue to obtain an imprinted product.
[0073] The imprinted product obtained above was eluted with a methanol / acetic acid mixture (ratio 9:1) eluent, stirred and eluted for 22 hours to remove the phenol template molecules on the imprinted reaction product. The washed imprinted reaction product was dried in a vacuum freeze dryer for 13 hours to finally obtain a gangue-based surface molecular imprinted adsorption material.
[0074] 0.2 g of gangue-based surface molecular imprinting adsorption material was taken and adsorbed with 20 mL of phenol solution with a mass concentration of 500 mg / L. Samples of the adsorbed solution were extracted at set times (5, 10, 15, 20, 30, 40, 60, 80, 100 and 120 min), and the content of phenol was determined by ultraviolet spectroscopy to calculate the adsorption amount of the gangue-based surface molecular imprinting adsorption material.
[0075] Take 0.2g of gangue-based surface molecular imprinting adsorption material and 0.2g of gangue, and place them in 20mL of phenol, hydroquinone and p-nitrophenol mixed solution, where the mass concentration of the three in the mixed solution is 500mg / L. Extract the adsorbed solution sample within the set time of 60min, and determine the content of phenol, hydroquinone and p-nitrophenol by ultraviolet spectroscopy to calculate the selectivity of the adsorption material.
[0076] Example 6
[0077] Raw material pretreatment: First, the large pieces of coal gangue were ground to 300 mesh; then, the powder was calcined at 800°C for 5 h; then, 14 mol / L hydrochloric acid was used for acid leaching for 6 h to finally obtain modified coal gangue powder.
[0078] Take 1g of phenol, 0.8g of modified coal gangue powder and 3mL of methacrylic acid, dissolve them in 30mL of acetonitrile solvent, introduce nitrogen for 5 minutes and then seal, and magnetically stir for 2h at 30℃ with a stirring speed of 450r / min; then add 2.0mL of ethylene glycol dimethacrylate and 0.2g of azobisisobutyronitrile, introduce nitrogen again for 5 minutes and then seal, and magnetically stir for 24h at 70℃ with a stirring speed of 400r / min. Phenol and methacrylic acid modify the pores of the modified coal gangue to obtain an imprinted product.
[0079] The imprinted product obtained above was eluted with a methanol / acetic acid mixture (ratio 9:2) and stirred for 24 hours to remove the phenol template molecules on the imprinted reaction product. The washed imprinted reaction product was dried in a vacuum freeze dryer for 12 hours to finally obtain a gangue-based surface molecular imprinted adsorption material.
[0080] 0.2 g of gangue-based surface molecular imprinting adsorption material was taken and adsorbed with 20 mL of phenol solution with a mass concentration of 500 mg / L. Samples of the adsorbed solution were extracted at set times (5, 10, 15, 20, 30, 40, 60, 80, 100 and 120 min), and the content of phenol was determined by ultraviolet spectroscopy to calculate the adsorption amount of the gangue-based surface molecular imprinting adsorption material.
[0081] Take 0.2g of gangue-based surface molecular imprinting adsorption material and 0.2g of gangue, and place them in 20mL of phenol, hydroquinone and p-nitrophenol mixed solution, where the mass concentration of the three in the mixed solution is 500mg / L. Extract the adsorbed solution sample within the set time of 60min, and determine the content of phenol, hydroquinone and p-nitrophenol by ultraviolet spectroscopy to calculate the selectivity of the adsorption material.
[0082] Example 7
[0083] Raw material pretreatment: First, the large pieces of coal gangue were ground to 200 mesh (see the attached SEM analysis). Figure 1 a); then, the powder was calcined at 700°C for 3 h, and then acid-leached with 12 mol / L hydrochloric acid for 4 h to obtain modified gangue powder (the scanning electron microscope analysis of which is shown in the attached Figure 1 c).
[0084] Take 1g of phenol, 0.8g of modified coal gangue powder and 3mL of methacrylic acid, dissolve them in 25mL of acetonitrile solvent, introduce nitrogen for 5min and then seal, and magnetically stir for 1h at 30℃ with a stirring speed of 400r / min; then add 1mL of ethylene glycol dimethacrylate and 0.15g of azobisisobutyronitrile, introduce nitrogen again for 10min and then seal, and magnetically stir for 22h at 70℃ with a stirring speed of 450r / min. Phenol and methacrylic acid modify the pores of the modified coal gangue to obtain an imprinted product.
[0085] The imprinted product obtained above was eluted with a methanol / acetic acid mixture (ratio 9:1) eluent, stirred and eluted for 24 hours to remove the phenol template molecules on the imprinted reaction product. The washed imprinted reaction product was dried in a vacuum freeze dryer for 14 hours to finally obtain a gangue-based surface molecular imprinted adsorption material.
[0086] 0.2 g of gangue-based surface molecular imprinting adsorption material was taken and adsorbed with 20 mL of phenol solution with a mass concentration of 500 mg / L. Samples of the adsorbed solution were extracted at set times (5, 10, 15, 20, 30, 40, 60, 80, 100 and 120 min), and the content of phenol was determined by ultraviolet spectroscopy to calculate the adsorption amount of the gangue-based surface molecular imprinting adsorption material.
[0087] Take 0.2g of gangue-based surface molecular imprinting adsorption material and 0.2g of gangue, and place them in 20mL of phenol, hydroquinone and p-nitrophenol mixed solution, where the mass concentration of the three in the mixed solution is 500mg / L. Extract the adsorbed solution sample within the set time of 60min, and determine the content of phenol, hydroquinone and p-nitrophenol by ultraviolet spectroscopy to calculate the selectivity of the adsorption material.
[0088] Table 1 Adsorption effect of gangue-based surface molecularly imprinted adsorption materials prepared in Examples 1-7 on phenols
[0089]
[0090] It can be seen from Table 1 above that the gangue-based surface molecular imprinting adsorption material prepared in Example 1 has the best selective adsorption effect on phenols, wherein the adsorption capacities of p-phenol, hydroquinone and p-nitrophenol are 46.12 mg / g, 32.25 mg / g and 29.18 mg / g respectively.
[0091] The method for preparing a gangue-based surface molecular imprinting adsorption material proposed in the present invention has the following advantages:
[0092] 1) Environmental protection and resource recycling: The present invention uses cheap and readily available coal gangue as a carrier, fully utilizes waste resources, reduces the pollution of coal gangue to the environment, conforms to the concept of green environmental protection, and reduces production costs while utilizing resources.
[0093] 2) Efficient preparation process and performance: Through simple calcination and modification processes, coal gangue is successfully converted into a surface molecular imprinting adsorption material with a large specific surface area and suitable pore structure. This process significantly improves the adsorption capacity and selectivity of the material, meeting the needs of efficient separation and detection. The excellent chemical stability of coal gangue enables the material to remain stable for a long time under various chemical reactions and environmental conditions, thereby extending its service life.
[0094] 3) Excellent selective adsorption performance: The gangue-based material after molecular imprinting treatment showed excellent selectivity for mixed solutions of various phenolic molecules such as phenol, hydroquinone and p-nitrophenol, demonstrating its wide application potential in adsorption, separation and detection.
[0095] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a gangue-based surface molecularly imprinted adsorption material, characterized in that: The steps include: calcining and acid leaching the gangue powder to obtain modified gangue powder; Using modified gangue powder as a carrier, phenol and methacrylic acid were added to acetonitrile solvent under an inert atmosphere for a preliminary reaction, and then a cross-linking agent and an initiator were added to carry out a surface molecular imprinting reaction to obtain an imprinting reaction product. The imprinting reaction product is treated to obtain the gangue-based surface molecular imprinting adsorption material.
2. The method for preparing the gangue-based surface molecularly imprinted adsorption material according to claim 1, characterized in that: The modified coal gangue powder is specifically obtained as follows: The coal gangue is ground to 200-300 meshes; the coal gangue powder is calcined at 700-800°C; and then acid-leached with 12-14 mol / L hydrochloric acid to obtain modified coal gangue powder.
3. The method for preparing the gangue-based surface molecularly imprinted adsorption material according to claim 2, characterized in that: The calcination time is 3h~5h, and the acid leaching time is 4h~6h.
4. The method for preparing the gangue-based surface molecularly imprinted adsorption material according to claim 1, characterized in that: The mass ratio of phenol, modified coal gangue powder and methacrylic acid is (1.0-1.2): (0.8-1.0): (3-5).
5. The method for preparing the gangue-based surface molecularly imprinted adsorption material according to claim 1, characterized in that: The added crosslinking agent is ethylene glycol dimethacrylate, and the added initiator is azobisisobutyronitrile.
6. The method for preparing the gangue-based surface molecularly imprinted adsorption material according to claim 5, characterized in that: The mass ratio of ethylene glycol dimethacrylate to azobisisobutyronitrile is (1-2):(0.15-0.20).
7. The method for preparing the gangue-based surface molecularly imprinted adsorption material according to claim 1, characterized in that: The temperature of the preliminary reaction is controlled at 20°C to 30°C, and the reaction time of the preliminary reaction is 1h to 2h; The temperature of the surface molecular imprinting reaction is controlled at 60°C to 70°C, and the reaction time of the surface molecular imprinting reaction is 22h to 24h; The above reactions were all carried out under an inert atmosphere, which was formed by introducing nitrogen into the reaction system and sealing it.
8. The method for preparing the gangue-based surface molecularly imprinted adsorption material according to claim 1, characterized in that: The imprinting reaction product is treated to obtain a gangue-based surface molecular imprinting adsorption material, specifically: The imprinting reaction product is placed in an eluent and stirred, and vacuum dried to obtain a gangue-based surface molecular imprinting adsorption material; The eluent is a mixture of methanol and acetic acid.
9. The method for preparing the gangue-based surface molecularly imprinted adsorption material according to claim 8, characterized in that: The volume ratio of methanol to acetic acid is 9:1-9:2; the stirring time is 22h-24h; and the vacuum drying is carried out in a vacuum freeze dryer for 12h-14h.
10. A coal gangue-based surface molecular imprinting adsorption material, characterized in that: The method is prepared by any one of claims 1 to 9.